(untitled) (Ustozlar uchun, 2025)
In this article, the poem “Motherland” by the famous Uzbek and Russian poet Alexander Feinberg is linguistically analyzed. The poem awakens feelings of loyalty to the Motherland and respect for every inch of its soil in the human heart. Feinberg embodied the pain and happiness in the heart in the image of the Motherland using the means of artistic imagery - allegory, symbol and parallelism.